Fluid management layer for absorbent article
The absorbent articles incorporate a card-processed staple fiber nonwoven fluid management layer to address issues of false detections and ink blowthroughs, improving the performance and reliability of absorbent articles.
Patent Information
- Application Number
- JP2021557089
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-03-27
AI Technical Summary
There is a need for absorbent articles with visual signals that avoid false detections in online visual systems and reduce the likelihood of ink blowthroughs.
The absorbent articles include a topsheet, a backsheet, and an absorbent core with a fluid management layer between the topsheet and the absorbent core. The fluid management layer is made of card-processed staple fiber nonwoven material with multiple fibers, which reduces false detections and ink blowthroughs.
The solution effectively reduces the likelihood of false detections in visual systems and minimizes ink blowthroughs, enhancing the performance and reliability of absorbent articles.
Smart Images

Figure 0007667088000003 
Figure 0007667088000004 
Figure 0007667088000005
Abstract
Description
[Technical field]
[0001] SUMMARY The present disclosure relates generally to absorbent layers for disposable absorbent articles having carded staple fiber nonwovens with improved performance characteristics. [Background technology]
[0002] Disposable absorbent articles, such as feminine hygiene products, taped diapers, panty diapers, and incontinence products, are designed to absorb fluids from the wearer's body. Users of such disposable absorbent articles have several concerns. One of the biggest concerns is related to leakage of discharged fluids from the absorbent article. Leakage from products such as sanitary pads, diapers, sanitary napkins, and incontinence pads is a significant concern.
[0003] To address leakage concerns, many manufacturers have attempted to reassure consumers regarding their product leakage capacity. Some manufacturers may choose a combination of methods to do this. For example, advertising may be used to indicate the volume of liquid the absorbent article can hold. Some manufacturers have also begun to provide visual signals that are visible from the wearer-facing side of the absorbent article.
[0004] These visual signals can be utilized to highlight features of the absorbent article that may normally be hidden from the consumer. For example, the full extent of the absorbent system within the absorbent article may not be readily discernible to the naked eye. However, providing a visual signal can convince the consumer that adequate absorbent capacity is present.
[0005] Providing a visual signal that is visible from the wearer-facing side of an absorbent article can be problematic. For example, if the visual signal is provided on the topsheet of the absorbent article, rub-off issues become a major concern. Specifically, the ink may bleed onto the wearer's skin, which may not only negatively affect the consumer's perception of the article, but may also lead to negative publicity for the absorbent article and its manufacturer.
[0006] Providing a visual signal on a layer below the garment-facing surface can have its own challenges. For example, the web on which the ink is deposited must be substantial enough to withstand ink blow-through, which occurs when ink passes through the web and "sprays" onto the carrier belt. This ink can contaminate the belt and lead to poor quality visual signals for subsequent absorbent articles. Additionally, the web on which the ink is deposited must be substantial enough so that the visual signal is properly aligned with the online vision system. Specifically, if the printed web is too porous, the online vision system may treat open areas in the web as defects, thereby inducing false positives. This can lead to slowdowns in production time as well as significant loss of revenue. Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, there is a need to produce absorbent articles with visual signals that avoid false positives in on-line vision systems and reduce the possibility of ink blow-through. [Means for solving the problem]
[0008] The absorbent article of the present disclosure includes a topsheet, a backsheet, and an absorbent core disposed between the topsheet and the backsheet. A fluid management layer is disposed between the topsheet and the absorbent core. A visual signal is printed on the fluid management layer, the visual signal being visible through the topsheet.
[0009] The fluid management layer includes a carded staple fiber nonwoven material that includes a plurality of fibers. The combination of the plurality of fibers reduces the possibility of false positives from a visual system inspecting the visual signal and reduces the possibility of ink blow-through. In one particular implementation, the fluid management layer includes an integrated carded nonwoven having a basis weight of about 40 grams per square meter (gsm) to about 120 gsm, the fluid management layer includes a plurality of absorbent fibers, a plurality of stiffening fibers, and a plurality of elastic fibers, the absorbent fibers comprising about 20% to about 75% by weight, the stiffening fibers comprising about 10% to about 40% by weight of bicomponent fibers, and the elastic fibers comprising about 20% to about 40% by weight, the fluid management layer having a first side and a second side, and a greater number of absorbent fibers present on the first side or the second side relative to the other. [Brief description of the drawings]
[0010] While the specification concludes with claims particularly pointing out and distinctly claiming the subject matter regarded as the invention, it is believed that the invention will be better understood from the following description read in conjunction with the accompanying drawings, in which: Some of the figures may be simplified by the omission of selected elements for the purpose of more clearly showing other elements. The omission of such elements in some of the figures does not necessarily indicate the presence or absence of a particular element in any of the illustrative embodiments, unless expressly depicted in the corresponding written description. None of the drawings are necessarily to scale. [Figure 1A] 1 is a schematic diagram of a disposable absorbent article constructed in accordance with the present disclosure. [Figure 1B] FIG. 1B is a schematic diagram of an absorbent system of the disposable absorbent article shown in FIG. 1A. [Diagram 2] FIG. 1 is a schematic diagram of a process that can be used to construct the fluid management layer of the present disclosure. [Diagram 3] 1 is a schematic elevation view of a fluid management layer constructed in accordance with the present disclosure; [Figure 4] FIG. 1 is a plan view of an exemplary absorbent system according to the present disclosure. [Diagram 5]1 is an elevational view illustrating an exemplary absorbent system according to the present disclosure. [Figure 6] FIG. 2 is an elevational view of another exemplary absorbent system according to the present disclosure. [Figure 7] 1 is a schematic cross-sectional view of an absorbent system according to the present disclosure. [Figure 8] 1 is a side-by-side depiction of a photographic comparison of stain size on absorbent articles. [Figure 9] 1 is a side-by-side depiction of a photographic comparison of stain size on absorbent articles. [Figure 10] 1 is a SEM image showing synthetic and viscose fibers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] As used herein, the following terms shall have the meanings specified below.
[0012] "Absorbent article" refers to a wearable device that absorbs and / or contains liquids, and more specifically, to a device that is placed against or in proximity to the body of a wearer to absorb and contain various exudates discharged from the body. Absorbent articles can include diapers, training pants, adult incontinence undergarments (e.g., liners, pads, and briefs), and / or feminine hygiene products.
[0013] A "longitudinal" direction is a direction extending parallel to the largest linear dimension of an article, typically the longitudinal axis of the article, including directions within 45° of the longitudinal direction. As used herein, the "length" of an article or a component thereof generally refers to the size / distance of the largest linear dimension of the article or part thereof, or typically refers to the size / distance of its longitudinal axis.
[0014] The "lateral" or "transverse" direction is the direction perpendicular to the longitudinal direction, i.e., in the same plane as the majority and longitudinal axis of the article, and the transverse direction is parallel to the transverse axis. As used herein, the "width" of an article or component thereof refers to the size / distance of the dimension perpendicular to the longitudinal direction of the article or component thereof, i.e., perpendicular to the length of the article or component thereof, and typically refers to the distance / size of the dimension parallel to the transverse axis of the article or component.
[0015] The "Z direction" is perpendicular to both the longitudinal and transverse directions.
[0016] As used herein, "machine direction" or "MD" means the direction parallel to the flow of carded staple fiber nonwoven fabrics through a nonwoven fabric making machine and / or absorbent article product manufacturing equipment.
[0017] As used herein, "Cross Machine Direction" or "CD" means the direction parallel to the width of a carded staple fiber nonwoven fabric making machine and / or absorbent article product manufacturing equipment and perpendicular to the machine direction.
[0018] As used herein, the term "integrated" is used to describe fibers of a nonwoven material that are twisted, entangled, and / or pushed / pulled in the positive and / or negative Z direction (thickness direction of the nonwoven material). Some exemplary processes for integrating fibers of a nonwoven web include spunlace and needlepunch. Spunlace uses multiple high-pressure water jets to entangle the fibers. Needlepunch uses needles to push and / or pull the fibers to entangle them with other fibers in the nonwoven. This mode of integration does not require adhesives or binders to hold the fibers together in the fluid management layer.
[0019] As used herein, the term "carded" is used to describe the structural characteristics of the fluid management layer described herein. Carded nonwovens use fibers cut to a specific length, also known as "staple filaments". The staple filaments may be of any suitable length. For example, the staple filaments may have a length of up to 120 mm, or may have a length as short as 10 mm. However, when a particular group of fibers is staple filaments, such as viscose fibers, the length of each of the viscose fibers in the carded nonwoven is generally the same, i.e., staple length. It is worth noting that when additional staple fiber length fiber types are included, such as polypropylene fibers, the length of each of the polypropylene fibers in the carded nonwoven is also generally the same. However, the staple length of the viscose and the staple length of the polypropylene may be different.
[0020] In contrast, continuous filaments, such as from spunbond or meltblown processes, do not result in staple length fibers. Instead, these filaments are of indefinite length and are not cut to specific lengths as described for staple length fibers.
[0021] The carded integrated nonwoven as disclosed herein can be used in a variety of disposable absorbent articles, but is particularly useful in diapers, feminine hygiene products, and incontinence products such as sanitary napkins and incontinence pads. The fluid management layer of the present disclosure is particularly useful when a visual signal is printed thereon. A schematic cross-sectional view of an exemplary absorbent article is shown in FIG. 1A.
[0022] The inventors have found that when the fluid management layer includes a visual signal, the opacity of the nonwoven material affects the likelihood of inducing a false positive in a visual system. Additionally, the inventors have found that opacity also correlates with the amount of ink blow-through during the printing process. Ink blow-through is the amount of ink that passes through the nonwoven material during the printing process. In general, ink blow-through is not viewed as a good occurrence. Rather, ink blow-through can contaminate web processing equipment and leave traces of ink on the subsequent web where the ink may be undesirable. The opacity of the integrated carded nonwoven of the present disclosure is described in more detail below.
[0023] 1A and 1B, an absorbent article 10 according to the present disclosure comprises a topsheet 20, a backsheet 50, and an absorbent core 40 disposed between the topsheet 20 and the backsheet 50. A fluid management layer 30 is disposed between the topsheet 20 and the backsheet 50, and in certain cases between the topsheet 20 and the absorbent core 40. The absorbent article has a wearer-facing side 60 and an opposing garment-facing side 62. The wearer-facing side 60 consists primarily of the topsheet 20, and the garment-facing side 62 consists primarily of the backsheet 50. Additional components may be included on either the garment-facing side 60 and / or the garment-facing side 62. For example, if the absorbent article is an incontinence pad, a pair of barrier cuffs extending generally parallel to the longitudinal axis L of the absorbent article 10 may form part of the wearer-facing side 60. Similarly, a fastening adhesive may be present on the backsheet 50 and form part of the garment-facing side 62 of the absorbent article.
[0024] The fluid management layer 30 includes opposed edges 32A and 32B that may extend generally parallel to the transverse axis T. The fluid management layer 30 also includes side edges 31A and 32B that may extend generally parallel to the longitudinal axis L. Similarly, the absorbent core 40 includes semi-lateral edges 42A and 42B that may extend generally parallel to the transverse axis T. The absorbent core 40 may also include side edges 41A and 41B that extend generally parallel to the longitudinal axis L.
[0025] As shown in the figures, each of edges 32A and 32B of the fluid management layer 30 can be disposed longitudinally outboard of the absorbent core 40. However, this is not necessary. For example, edges 32A and / or 32B can be coextensive with the absorbent core 40, or edges 32A and / or 32B can be disposed longitudinally inboard of edges 42A and / or 42B of the absorbent core 40.
[0026] Similarly, side edges 31A and / or 31B may be disposed transversely outboard of side edges 41A and / or 41B of absorbent core 40. Alternatively, side edges 31A and / or 31B may be coextensive with side edges 41A and / or 41B of absorbent core 40.
[0027] As previously mentioned, the fluid management layer 30 is a consolidated, carded nonwoven material. A schematic diagram of a carding and consolidation process suitable for forming the fluid management layer 30 of the present disclosure is shown in FIG. 2. As shown in the figure, a plurality of carding machines 210, 220, and 230 can each form a carded nonwoven web (e.g., 214, 224, and 234, respectively), which is transferred to a carrier belt 240. Each of the carded nonwoven webs 214, 224, and 234 can be fed to the carrier belt 240 via a web chute 212, 222, and 232, respectively. It is also worth noting that after the carded nonwoven 214 is deposited on the carrier belt 240, the carded nonwoven 224 is deposited on the carrier belt 240 on the first carded nonwoven 214. Similarly, a third carded nonwoven web 234 is deposited on the second carded nonwoven 224 and the first carded nonwoven 214 on the carrier belt 240. Each of the first, second, and third carded nonwoven webs 214, 224, and 234 are then fed to a consolidation process 250 which utilizes either needles and / or high pressure water jets to entangle the fibers of the first, second, and third carded nonwoven webs. Both carding and consolidation processes are well known in the art.
[0028] It is worth noting that the configuration shown in the schematic diagram of FIG. 2 allows for various configurations of the fluid management layer. However, it is important that the fluid management layer of the present disclosure has sufficient openness to allow for rapid fluid acquisition. Furthermore, for rapid fluid acquisition, the fluid management layer of the present disclosure needs to ensure good fluid distribution to the absorbent core. The inventors have found that the more efficient the fluid management layer is in distributing fluid to the absorbent core, the smaller the stain intensity and / or stain size visible through the topsheet. Unfortunately, the openness of the fluid management layer can also be problematic, as the vision system may see the open areas as defects in the visual signal. With this in mind, the carded webs, i.e., 214, 224, and / or 234, can be different from each other. For example, one of the carded webs may include a different fiber blend than the others. Specifically, assuming that the first carded web is located closest to the wearer-facing surface of the absorbent article, the fiber selection of the first carded web 214 can be such that this web is associated with a greater openness. The second carded web 224 may be similarly configured. In contrast, the third carded web 234 may be configured to reduce the likelihood of false positives by a vision system that "sees" open areas as defects. The third carded web 234 may be configured to effectively distribute liquid soil to the underlying absorbent core in combination with or independent of reducing false positives. If the fiber compositions of the two cards are different, the nonwoven is called heterogeneous. If all the cards have the same fiber blend, the nonwoven is called homogeneous.
[0029] If the first carded web 214 and the second carded web 224 contain the same fiber blend, the fluid management layer of the present disclosure can be processed through two cards instead of three. However, such processing can delay production of the first carded layer 214 having a much higher basis weight than the basis weight of the third carded web 234.
[0030] 1A-3, the first carded nonwoven 214, the second carded nonwoven 224 (optionally, as described above), and the third carded nonwoven 234 are integrated. Once integrated, they cannot be separated manually, at least without significant effort and time. Each carded nonwoven web forms a layer throughout the fluid management layer 30. Each layer can maintain its unique properties over at least a portion of the layer along the z-direction, even when integrated into the larger fluid distribution layer 30. The fluid management layer 30 provides capillary suction that "pull" fluid through the topsheet 20 competing for trickle / low flow conditions. The fluid management layer 30 can also contain gushes by efficiently utilizing the absorbent core 40 by providing a distribution function, as well as provide intermediate storage until the absorbent core 40 is able to accept fluid.
[0031] The fluid management layer 30 has a first surface 300A and an opposing second surface 300B. The fluid distribution layer 30 includes two or more layers along the Z direction between the first surface 300A and the second surface 300B. The fluid distribution layer 30 may have a basis weight of up to 120 grams per square meter (gsm), or a basis weight of up to 100 gsm, or a basis weight in the range of about 30 gsm to about 120 gsm, or in the range of about 40 gsm to about 100 gsm, or in the range of about 45 gsm to about 70 gsm, or in the range of about 50 gsm to about 55 gsm, including any value within these ranges and any range defined by these ranges. In one particular example, the fluid management layer 30 may have a basis weight of about 50 gsm to about 75 gsm.
[0032] The fluid management layer 30 may have a caliper of between 0.6 millimeters (mm) and 1.5 mm, including any value within these ranges and any ranges defined by these ranges.
[0033] Because the fibers are integrated, the fluid management layer 30 does not require adhesives or latex binders for stabilization. Additionally, the carded staple fiber nonwoven of the fluid distribution layer can be manufactured from any suitable combination of fiber types that provides the desired performance characteristics. For example, the fluid management layer 30 can include a combination of stiffening fibers, absorbent fibers, and elastic fibers.
[0034] To enhance the stabilizing effect of consolidation, crimped fibers can be used. As described in more detail below, the fluid management layer of the present disclosure can include absorbent fibers, stiffening fibers, and elastic fibers. One or more of these fibers can be crimped prior to consolidation. For example, when synthetic fibers are used, they can be mechanically crimped by interlocking teeth. Also, with respect to absorbent fibers, they can be mechanically crimped and / or have a chemically induced crimp due to thickness changes formed during formation of the absorbent fibers.
[0035] The fluid management layer 30 as a whole can include from about 20% to about 75%, from about 25% to about 60%, from about 30% to about 50% by weight of absorbent fibers, including any value within these ranges and any ranges defined by these ranges. In one particular example, the fluid management layer 30 can include from about 40% to about 50% by weight of absorbent fibers.
[0036] Similarly, the fluid management layer 30 may, overall, comprise from about 10% to about 50%, from about 13% to about 40%, from about 20% to about 35%, from about 25% to about 30% by weight of elastic fibers, including all values within these ranges and any ranges defined by these ranges. In one particular example, the fluid management layer 30 may comprise from about 26% to about 33% by weight of elastic fibers.
[0037] Additionally, the fluid management layer 30 may include from about 1% to about 50%, from about 10% to about 40%, or from about 20% to about 30% stiffening fibers by weight, including all values within these ranges and any ranges defined by these ranges. In one particular example, the fluid management layer 30 may include from about 20% to about 30% stiffening fibers by weight.
[0038] Whether the fluid management layer is used in an adult incontinence article or a menstrual article, the ability of the fluid management layer to capture liquid waste from the topsheet and draw the liquid far enough away from the topsheet so that the topsheet does not feel wet is crucial. In achieving this, the inventors have found that while absorbent fibers adjacent to the topsheet aid in drawing liquid from the topsheet, too many absorbent fibers can lead to a topsheet that feels wet. Thus, the amount of absorbent fibers in the layer closest to the topsheet is crucial. That is, too many absorbent fibers in the first carded nonwoven web 214 and / or the second carded nonwoven web 224 can lead to a topsheet that feels wet (assuming the first carded nonwoven 214 and the second carded nonwoven 224 are located closer to the topsheet than the third carded nonwoven 234).
[0039] Additionally, while a higher weight percentage of absorbent fiber may be beneficial for more viscous fluid waste (e.g., menstrual fluid), the introduction of a higher weight percentage of absorbent fiber may also adversely affect the elasticity and stiffness of the fluid management layer. Also, too low a weight percentage of absorbent fiber may result in a topsheet that feels more "wet," which may result in a negative perception of the product in consumer sentiment.
[0040] Furthermore, the inventors have found that the fluid management layer can include sufficient void volume adjacent to the topsheet to allow for rapid fluid acquisition. As mentioned above, the tradeoff is that this beneficial void volume can also induce false positives in the visual system inspecting the visual signal. In general, for a given basis weight, larger diameter fibers can provide more void volume between adjacent fibers compared to smaller diameter fibers. Therefore, the fiber diameter of the fibers in the layer close to the topsheet is also crucial. That is, if the diameter of the fibers in the first carded nonwoven 214 and / or the second carded nonwoven 224 is too small, this can negatively affect the formed void volume created for rapid fluid acquisition (assuming that the first carded nonwoven 214 and the second carded nonwoven 224 are located closer to the topsheet 20 than the third carded nonwoven 234). This can also lead to a topsheet that feels wetter.
[0041] There are many possible ways to address the opacity indicators that the inventors have associated with false positives of the vision system. As discussed above, larger fibers may create more void volume than smaller fibers. Also, smaller fibers may produce higher opacity than larger fibers. However, the placement of these smaller fibers in the fluid management layer may enhance or adversely affect the performance of the fluid management layer. For example, the placement of smaller fibers adjacent to the topsheet may significantly reduce the void volume of the fluid management layer depending on the weight percentage in the first layer and / or second layer.
[0042] In view of the above, the inventors have carefully selected not only the fiber type for each layer within the fluid management layer, but also the diameter of each fiber type. The fiber types of the individual layers are described in further detail below. It is worth noting that the following discussion of fiber types within the layers of the fluid management layer assumes that the first carded nonwoven web 214 is located closer to the topsheet than the third carded nonwoven web 234.
[0043] The first carded nonwoven 214 (or first layer 214) can include absorbent fibers, stiffening fibers, and elastic fibers. To provide sufficient void volume and ensure that liquid waste is removed from the topsheet in a timely manner, the first layer 214 can include from about 10 percent to about 50 percent. More preferably, it includes from about 12% to about 40% by weight, or most preferably from about 15% to about 30% by weight absorbent fibers, with all values within these ranges and any ranges defined by these ranges being specifically recited. In one particular example, the first layer 214 can include from about 15% to about 25% by weight absorbent fibers.
[0044] The first layer 214 can further comprise about 20% to about 75% by weight of elastic fibers, more preferably about 30% to about 60% by weight, or most preferably about 40% to about 50% by weight, including these ranges and any value within any range defined by these ranges. In one particular embodiment, the first layer 214 can comprise about 40% to about 50% by weight of elastic fibers.
[0045] The first layer 214 can further comprise between about 20% and about 75% by weight, more preferably between about 25% and about 60% by weight, or most preferably between about 30% and about 45% by weight stiffening fibers, including any value within these ranges and any ranges defined by these ranges. In one particular embodiment, the first layer 214 can comprise between about 30% and about 45% by weight stiffening fibers.
[0046] The second carded nonwoven 224 (or second layer 224) can be configured similarly to the first layer 214, or at least within the ranges specified for the first layer. Such a configuration of the second layer 224 is believed to facilitate some manufacturing. Also, recall that the second layer 224 is optional. However, because the second layer 224 is positioned farther from the topsheet 20 than the first layer 214, the void volume can be adjusted slightly downward. Thus, using smaller diameter fibers in the second layer 224 can help overcome the problem of false positive vision systems discussed above.
[0047] With respect to the third carded nonwoven 234 (or third layer 234), the configuration of this layer may vary. If the third layer 234 forms a portion of the second surface 300B of the fluid management layer 30, the third layer 234 may be configured to reduce the likelihood of false positives associated with visual signal detection in a vision system. Additionally, the third layer 234 may have sufficient capacity to capture and distribute fluid within the void volume of the first layer 214 and / or second layer 224. To reduce the likelihood of false positives associated with visual signal detection by a vision system, the inventors have found that smaller diameter fibers may be used in the third layer 234. Absorbent fibers may also be used to appropriately impart the desired capture and distribution characteristics. In some embodiments, the third layer 234 can include from about 50% to about 100% by weight, more preferably from about 60% to about 90% by weight, or most preferably from about 70% to about 80% by weight absorbent fibers, specifically including all values within these ranges and any ranges defined by these ranges. In one particular embodiment, the third layer 234 can include 100 percent absorbent fibers.
[0048] As previously mentioned, the fluid management layers of the present disclosure can provide high fluid handling and opacity properties to their corresponding absorbent articles. If caliper, resilience, and soft cushion-like feel are the objectives, the weight percentage of stiffening fibers can be equal to or greater than the weight percentage of elastic fibers. The weight percentage of absorbent fibers can be greater than the weight percentage of elastic and / or stiffening fibers. The latter is especially true when the fluid management layers of the present disclosure are used in adult incontinence articles. In general, a higher weight percentage of absorbent fibers is believed to be beneficial for absorbing fluid waste quickly. However, given the proximity of absorbent fibers to the topsheet, it is beneficial for the absorbent core to dehydrate the absorbent fibers. A larger percentage of absorbent fibers typically requires a larger core to dehydrate the absorbent fibers. This generally translates to higher costs. With this in mind, the weight percentage ratio of absorbent fibers to stiffening fibers in the fluid management layers of the present disclosure can be from about 3:1 to about 1.2:1, more preferably from about 2.5:1 to about 1.3:1, and most preferably from about 2:1 to about 1.4:1, and all values within these ranges and any ranges defined by these ranges are specifically recited. Similarly, the weight percentage ratio of absorbent fibers to elastic fibers in the fluid management layers of the present disclosure can be from about 3:1 to about 1.3:1, more preferably from about 2.75:1 to about 1.5:1, or most preferably from about 2.5:1 to about 1.6:1, and all values within these ranges and any ranges defined by these ranges are specifically recited.
[0049] The fluid management layer of the present disclosure may include a heterogeneous structure. For example, as discussed above, the fluid management layer of the present disclosure may include a greater percentage of cellulose on one side of the fluid management layer relative to the opposing side. Thus, the first surface 300A may include a lower percentage of absorbent fibers than the opposing second surface 300B according to the SEM method for quantification of cellulose fibers. The fluid management layer of the present disclosure may have a fiber ratio of absorbent fibers on the first side to the second side (or vice versa) of about 5:1 to about 1.5:1, or more preferably about 4.5:1 to about 1.5:1, or most preferably about 4:1 to about 1.5:1.
[0050] With respect to the stiffening and elastic fibers in the third layer 234, as discussed above, the third layer must be able to capture and distribute fluid from the void volume of the first layer 214 and the second layer 224. Thus, the amount of either stiffening or elastic fibers must be carefully considered. As discussed above, no stiffening or elastic fibers are required (e.g., 0 weight percent) in the third layer 234. With this in mind, the third layer may include 0 weight percent to about 30 weight percent stiffening and / or elastic fibers, more preferably about 0 weight percent to about 25 weight percent, or most preferably about 0 weight percent to about 20 weight percent, all values within these ranges and any ranges defined by these ranges are recited.
[0051] 1A-3, if absorbent fibers are used, any suitable diameter of the absorbent fibers can be used. A suitable diameter measure can be related to the linear density. For the first layer 214 and / or the second layer 224, increased void volume may be desired, and therefore larger linear density values can be used. For example, the linear density of the absorbent fibers of the first layer 214 and / or the second layer 224 can range from about 1 dtex to about 4 dtex, more preferably from about 1.0 dtex to about 3.7 dtex, or most preferably from about 1.0 dtex to about 3.5 dtex, with all values within these ranges and any ranges defined by these ranges being recited. In one particular example, the absorbent fibers can have a dtex of about 1.7 dtex.
[0052] However, in the third layer 234, it may be necessary to reduce the linear density to aid in detection of the visual signal. Thus, the linear density of the absorbent fibers in the third layer 234 can be from about 1 dtex to about 3 dtex, more preferably from about 1.4 dtex to about 2.7 dtex, or most preferably from about 1.7 dtex to about 2.0 dtex, specifically reciting all values within these ranges and any ranges defined by these ranges. In one particular example, the absorbent fibers in the third layer 234 can have a dtex of about 1.7.
[0053] While it is technically possible to have absorbent fibers in the fluid management layers with varying linear densities, not all carding machines are suited to handle such inter-layer / layer-to-layer variations. To mitigate potential processing issues, the absorbent fibers in the fluid management layers may have the same linear density throughout all layers.
[0054] The absorbent fibers of the fluid management layer may have any suitable shape. Some examples include trilobal, "H", "Y", "X", "T", or round. Additionally, the absorbent fibers may be solid, hollow, or multi-hollow. Other examples of multi-lobal absorbent fibers suitable for use in the carded staple fiber nonwovens detailed herein are disclosed in U.S. Patent No. 6,333,108 to Wilkes et al., U.S. Patent No. 5,634,914 to Wilkes et al., and U.S. Patent No. 5,458,835 to Wilkes et al. The trilobal shape may improve wicking and improve masking. A suitable trilobal rayon is available from Kelheim Fibres and is sold under the trade name Galaxy. Each layer may include absorbent fibers of different shapes, as discussed above, although not all carding equipment is suitable for handling such variations between / between layers. In one particular example, the fluid management layer includes round absorbent fibers.
[0055] Any suitable absorbent fiber may be used. Some conventional absorbent fibers include cotton, rayon, or regenerated cellulose, or combinations thereof. In one example, the fluid management layer 30 may include viscose cellulose fibers. The absorbent fibers may include staple long fibers. The staple length of the absorbent fibers may range from about 20 mm to about 100 mm, or from about 30 mm to about 50 mm, or from about 35 mm to about 45 mm, and specifically recites all values within these ranges and any ranges defined by these ranges.
[0056] As mentioned above, in addition to the absorbent fibers, the fluid management layer may also include stiffening fibers. The stiffening fibers may be used to help provide structural integrity to the fluid management layer. The stiffening fibers help to increase the structural integrity of the absorbent fibers in the machine direction and cross machine direction, which may facilitate easier handling of the web when processing the fluid management layer for incorporation into a disposable absorbent article. With that in mind, the composition of the stiffening fibers, the weight percentage of the stiffening fibers, and the heat of processing should be carefully selected. The heat stiffening process is described below.
[0057] Any suitable stiffening fiber can be used. Some examples of suitable stiffening fibers include bicomponent fibers, including polyethylene and polyethylene terephthalate components or polyethylene terephthalate and copolyethylene terephthalate components. The components of the bicomponent fiber can be arranged in a core-sheath configuration, a side-by-side configuration, an eccentric core-sheath configuration, a trilobal configuration, and the like. In one particular embodiment, the stiffening fiber can include a bicomponent fiber having polyethylene / polyethylene terephthalate components arranged in a concentric core-sheath configuration, with the polyethylene being the sheath. As another example, a monocomponent fiber can be used, and the monocomponent component material can include polypropylene or polylactic acid (PLA). It is worth noting that these components, such as polypropylene and polylactic acid, can also be used in bicomponent fibers.
[0058] The stiffening fibers may be polyethylene terephthalate (PET) fibers or other suitable non-cellulosic fibers known in the art. The staple length of the stiffening fibers may range from about 28 mm to about 100 mm, or from about 37 mm to about 50 mm. Some carded staple fiber nonwoven fabrics have a staple length of about 38 mm to 42 mm. The PET fibers may have any suitable structure or shape. For example, the PET fibers may be round or other shapes such as helical, wavy oval, trilobal, wavy ribbon, etc. Furthermore, the PET fibers may be solid, hollow, or multi-hollow. In some embodiments of the carded staple fiber nonwoven fabric, the stiffening fibers may be fibers made from hollow / spiral PET. Optionally, the stiffening fibers may be helical crimped or flat crimped. The stiffening fibers may have a crimp value of from about 4 to about 12 crimps per inch (cpi), or from about 4 to about 8 cpi, or from about 5 to about 7 cpi, or from about 9 to about 10 cpi. Specific non-limiting examples of stiffening fibers may be obtained from Wellman, Inc. Ireland under the trade names H1311 and T5974. Other examples of stiffening fibers suitable for utilization in the carded staple fiber nonwoven fabrics detailed herein are disclosed in U.S. Patent No. 7,767,598 to Schneider et al.
[0059] Other suitable examples of stiffening fibers include polyester / coextruded polyester fibers. Stiffening fibers may be so-called bicomponent fibers, where the individual fibers are provided from different materials, usually a first and a second polymeric material. The two materials may be chemically different (thus the fibers are chemically heterogeneous) or may be chemically identical but differ only in their physical properties (thus the fibers are chemically homogeneous). For example, the intrinsic viscosities of the two materials may be different, which has been found to affect the crimp behavior of the bicomponent fibers. Bicomponent fibers suitable as stiffening fibers are side-by-side bicomponent fibers, as disclosed, for example, in WO 99 / 00098. Stiffening fibers may also be blends of bicomponent fibers with polyester fibers.
[0060] With particular reference to the cross-section of a bicomponent fiber made of a polypropylene / polyethylene fiber composition, the material with the higher softening temperature can provide the center portion (i.e., core) of the fiber. The core is typically responsible for the bicomponent fiber's ability to transmit forces and provide a certain degree of hardness or otherwise provide resilience to the structure. The outer coating (i.e., sheath) of the fiber core can have a lower melting point and is used to promote thermal bonding of substrates containing this type of fiber. In one embodiment, a polyethylene-coated polypropylene core is provided, in which about 50% by weight of the fiber material is polypropylene and about 50% by weight of the fiber material is polyethylene. Other quantitative amounts can, of course, be selected. For example, the bicomponent fiber can have a composition in which the polyethylene accounts for about 30% to about 70% by weight, and can also have a composition in which the polyethylene accounts for about 35% to about 65% by weight. In some embodiments, the bicomponent fiber can have a composition in which the polyethylene accounts for about 40% to about 60% by weight, or about 45% to about 55% by weight.
[0061] Another suitable bicomponent stiffening fiber is a circular cross-section fiber with a hollow space in the center that is helically crimped. Preferably, 10-15% of the cross-sectional area is hollow, more preferably 20-30% of the cross-sectional area is hollow. Without being bound by theory, it is believed that the helical crimping of the fiber is beneficial to the liquid acquisition and distribution behavior. It is presumed that the helical crimping increases the void space in the acquisition member formed by such fibers. In many cases, absorbent articles, when worn, are subjected to certain pressures exerted by the wearer, which may reduce the void space in the acquisition member. Having good permeability and sufficient void space available is important for good liquid distribution and transport. It is further believed that such bicomponent helically crimped fibers are suitable for maintaining sufficient void volume even when the acquisition member is exposed to pressure. Also, helically crimped fibers are believed to provide good permeability for a given fiber decitex value, and hollow fiber cross-sections allow for larger outer fiber diameters compared to compressed cross-sections, which appear to determine the permeability behavior of acquisition members formed by such fibers.
[0062] Any suitable diameter stiffening fibers can be used in the first layer 214 and / or the second layer 224. Suitable linear densities of the stiffening fibers can be from about 1.7 dtex to about 12 dtex, more preferably from about 4 dtex to about 10 dtex, or most preferably from about 5 dtex to about 7 dtex, specifically reciting all values within these ranges and any ranges defined by these ranges. In one particular example, for incontinence articles, the stiffening fibers can include polyethylene terephthalate / polyethylene fibers of 5.5 dtex to about 5.8 dtex.
[0063] Similar to the absorbent fibers in the third layer 234, the stiffening fibers included in the third layer 234 may have a lower linear density than those in the first and / or second layers. If the third layer 234 includes stiffening fibers, the linear density may range from about 0.9 dtex to about 6 dtex, more preferably from about 1.3 dtex to about 3 dtex, or most preferably from about 1.6 dtex to about 2.5 dtex, including all values within these ranges and any ranges defined by these ranges.
[0064] As mentioned above, the fluid management layer may be heat treated (heat stiffened). This heat treatment can create bond points between the stiffening fibers of the fluid management layer 30. Therefore, if the percentage of stiffening fibers is high, more bond points can be created. Too many bond points will give a much stiffer fluid management layer, which can have a negative impact on comfort. Therefore, the weight percentage of stiffening fibers is very important when designing an absorbent article.
[0065] Any suitable temperature can be utilized for the heat stiffening process, and the suitable temperature can be influenced in part by the chemical nature of the stiffening fiber components and by the fluid management layer being treated. The fluid management layer can be heat stiffened at a temperature of 132°C. It is also worth noting that to provide uniform stiffness properties across the fluid management layer, any heating operation should be set to provide uniform heating to the web of the fluid management layer. Even small variations in temperature can have a significant effect on the tensile strength of the fluid management layer.
[0066] As mentioned above, the fluid management layer of the present disclosure may further comprise elastic fibers. The elastic fibers may help the fluid management layer maintain its permeability. Any suitable diameter fiber may be used. For example, the elastic fibers may have a linear density of about 4 dtex to about 12 dtex, more preferably about 6 dtex to about 11 dtex, or most preferably about 8 dtex to about 10 dtex, specifically reciting all values within these ranges and any ranges defined by these ranges. In one particular example, the elastic fibers may have a linear density of hollow helical polyethylene terephthalate fibers of about 6.7 dtex to about 10 dtex.
[0067] It is worth noting that when smaller fiber diameters are used, the elasticity of the fluid management layer is expected to decrease, and the decrease in permeability of the fluid management layer is expected to be compensated for by the use of more fibers per gram with the same weight percent decrease in diameter.
[0068] Similar to the absorbent fibers in the third layer 234, the elastic fibers included in the third layer 234 may have a lower linear density than those in the first and / or second layers. If the third layer 234 includes elastic fibers, the linear density may range from about 0.9 dtex to about 12 dtex, more preferably from about 1.3 dtex to about 9 dtex, or most preferably from about 1.6 dtex to about 6 dtex, with all values within these ranges and any ranges defined by these ranges being specifically recited.
[0069] The elastic fibers can be any suitable thermoplastic fibers, such as polypropylene (PP), polyethylene terephthalate, or other suitable thermoplastic fibers known in the art. The staple length of the elastic fibers can range from about 20 mm to about 100 mm, or from about 30 mm to about 50 mm, or from about 35 mm to about 45 mm. The thermoplastic fibers can have any suitable structure or shape. For example, the thermoplastic fibers can be circular or have other shapes, such as helical, wavy oval, trefoil, wavy ribbon, and others. Furthermore, the PP fibers can be solid, hollow, or multi-hollow. The elastic fibers can be solid and round. Other suitable examples of elastic fibers include polyester / coextruded polyester fibers. Other suitable examples of elastic fibers include bicomponent fibers, such as polyethylene / polypropylene, polyethylene / polyethylene terephthalate, polypropylene / polyethylene terephthalate, and the like. These bicomponent fibers can be configured as sheath and core. Bicomponent fibers can provide a cost-effective means to increase the basis weight of a material while also allowing for optimization of the pore size distribution.
[0070] It is worth noting that the stiffening and elastic fibers must be carefully selected. For example, the chemical nature of the components of the stiffening and elastic fibers may be similar, but the elastic fiber must be selected such that the melting point of its constituent material is higher than that of the stiffening fiber. Otherwise, during heat treatment, the elastic fiber may bond to the stiffening fiber (or vice versa), resulting in an overly rigid structure.
[0071] Multiple samples were made and tested to evaluate their opacity and caliper. It was determined that opacity gives clues as to whether a particular sample reduces the likelihood of a false positive in a vision system evaluating a visual signal. Thirteen different samples were tested for opacity. Each of the samples was a hydroentangled, carded staple fiber nonwoven fabric that included multiple layers.
[0072] Sample Description: Sample 1: 50 gsm spunlace: The first, second, and third layers are homogenous and each have 25 percent trilobal rayon (3.3 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). Sample 1 is described in further detail in U.S. Patent Application Publication No. 2018 / 0098893.
[0073] Sample 2: 60 gsm spunlace: The first, second, and third layers are homogenous and each have 25 percent trilobal rayon (3.3 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). Sample 2 is described in further detail in U.S. Patent Application Publication No. 2018 / 0098893.
[0074] Sample 3: 50 gsm spunlace: The first and second layers were homogenous and each had 25 percent trilobal rayon (3.3 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 100 percent trilobal rayon (3.3 dtex).
[0075] Sample 4: 60 gsm spunlace: The first and second layers were homogenous and each had 25 percent trilobal rayon (3.3 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 100 percent trilobal rayon (3.3 dtex).
[0076] Sample 5: 50 gsm spunlace: The first and second layers were homogenous and each had 25 percent trilobal rayon (3.3 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 100 percent round rayon (1.7 dtex).
[0077] Sample 6: 60 gsm spunlace: The first and second layers were homogenous and each had 25 percent trilobal rayon (3.3 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 100 percent round rayon (1.7 dtex).
[0078] Sample 7: 50 gsm spunlace: The first and second layers were homogenous and each had 25 percent trilobal rayon (3.3 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (4.4 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 100 percent round rayon (1.7 dtex).
[0079] Sample 8: 60 gsm spunlace: The first and second layers were homogenous and each had 25 percent trilobal rayon (3.3 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (4.4 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 100 percent round rayon (1.7 dtex).
[0080] Sample 9: 55 gsm spunlace: The first and second layers were homogenous and each had 25 percent round viscose rayon (1.7 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 45 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 100 percent round rayon (1.7 dtex).
[0081] Sample 10: 110 gsm spunlace: The first and second layers were homogenous and each had 20 percent round viscose rayon (1.7 dtex), 40 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 40 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 80 percent viscose rayon (1.7 dtex) and 20 percent polyethylene terephthalate hollow spiral fiber (10 dtex).
[0082] Sample 11: 75 gsm spunlace: The first and second layers were homogenous and each had 20 percent round viscose rayon (1.7 dtex), 40 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 40 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The third layer had 80 percent viscose rayon (1.7 dtex) and 20 percent polyethylene terephthalate hollow spiral fiber (10 dtex).
[0083] Sample 12: 45 gsm spunlace: This sample had only two layers. The first layer had 20 percent viscose rayon round (1.7 dtex), 40 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 40 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The second layer had 80 percent viscose rayon (1.7 dtex) and 20 percent polyethylene terephthalate hollow spiral fiber (10 dtex).
[0084] Sample 13: 50 gsm spunlace: This sample had only two layers. The first layer had 20 percent viscose rayon round (1.7 dtex), 40 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 40 percent hollow spiral polyethylene terephthalate fiber (10 dtex). The second layer had 20 percent round viscose rayon (1.7 dtex), 20 percent polyethylene terephthalate / polyethylene bicomponent fiber (5.8 dtex), and 60 percent polypropylene fiber (1.3 dtex).
[0085] The inventors have determined that the fluid management layer should have an opacity of at least 48.5 percent to reduce the likelihood of false positives associated with vision system analysis of a visual signal. Table 1 shows the opacity data for each of the samples listed above.
[0086] [Table 1]
[0087] Again, the inventors have determined that an opacity of at least 48.5 percent is useful in preventing false positives in a vision system analyzing a visual signal. As shown in Table 1, Samples 4-11 and 13 were able to achieve average opacity values above 48.5 percent. As shown, each sample in the present disclosure can have an opacity (%) of 48.5 to about 70 percent, or more preferably 50 percent to about 65 percent, or most preferably about 55 percent to about 60 percent.
[0088] The inventors have also found that in addition to opacity requirements, the tensile strength of the web can also be an important factor. For example, processing problems can occur when the tensile strength of the web is less than about 18 Newtons in the MD and / or less than about 5 Newtons in the CD. For example, when the web width (CD) is less than 80 mm, a tensile strength of more than 18 N in the MD and / or more than 5 N in the CD can facilitate web handling. When the web width is larger, a lower tensile strength in the MD and / or CD can be sufficient to allow reliable web handling during processing. One of the problems that can occur due to a lower tensile strength in the MD and / or CD is stretching of the material roll, where the roll core stretches outward from the center of the roll. This can cause major web handling problems and cost and time loss.
[0089] The tensile strength (both MD and CD) of fluid management layers constructed in accordance with the present disclosure are shown in Table 2. Also shown are the tensile strengths in MD and CD of conventional fluid management layers. The calipers of these samples are also shown. Note that in Table 2, the sample constructed in accordance with the present disclosure is Sample 9. This conventional sample was 75 gsm and contained three homogenous layers. Each of the layers contained 35 percent trilobal viscose rayon (3.3 dtex), 40 percent polypropylene (6.7 dtex), and 25 percent hollow spiral polyethylene terephthalate (10 dtex).
[0090] [Table 2]
[0091] Thus, in a fluid management layer constructed according to the present disclosure, the tensile strength in the MD may be from about 19 N to about 50 N, more preferably from about 20 N to about 40 N, or most preferably from about 22 N to about 35 N, including these ranges and any values within any ranges defined by these ranges. Similarly, the tensile strength in the CD may be from about 5 N to about 15 N, more preferably from about 6 N to about 12 N, or most preferably from about 7 N to about 10 N, including these ranges and any values within any ranges defined by these ranges.
[0092] Furthermore, the inventors have unexpectedly found that the fluid management layer of the present disclosure, when used in a menstrual article, can reduce the size of stains on the article and / or can reduce the intensity of stains on the article. Each of these properties can have a significant impact on the wearer of the article. For example, the more intense the stain, e.g., the brighter the red, the closer the user perceives the liquid to be to the body. Similarly, the larger the stain, the greater the user's concern regarding the capacity of the absorbent article.
[0093] A number of samples were tested to measure the stain size. The stain intensity was observed in the photographs taken to assess the stain size.
[0094] Sample 14: 70 gsm spunlace: The first and second layers were homogenous and had 20 percent round viscose rayon (1.7 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fibers (5.8 dtex), and 50 percent polyethylene terephthalate fibers (6.7 dtex), respectively. The third layer had 80 percent round rayon (1.7 dtex) and 20 percent polyethylene terephthalate (6.7 dtex).
[0095] Sample 15: 55 gsm spunlace: A homogeneous blend across three layers, each having 40 percent viscose rayon (1.7 dtex), 40 percent polypropylene / polyethylene (1.7 dtex), and 20 percent polyethylene terephthalate (4.4 dtex).
[0096] FIG. 8 shows a side-by-side comparison of photographs 1000 of feminine hygiene pads with liquid soiling applied. Feminine hygiene pad samples 810A, 810B, and 810C had the fluid management layer of Sample 15, and feminine hygiene article samples 820A, 820B, and 820C had the fluid management layer of Sample 14. Samples 810A and 820A each had a film / carded nonwoven laminate topsheet and an airlaid absorbent core having a basis weight of 163 gsm. Samples 810B and 820B each had a film / spunbond nonwoven laminate topsheet and an airlaid absorbent core having a basis weight of 163 gsm. Samples 810C and 820C each had a film topsheet and an airlaid absorbent core having a basis weight of 163 gsm.
[0097] As shown, feminine hygiene pads 820A, 820B, and / or 820C show reduced stain size and / or reduced stain intensity. Further testing at a 15° incline showed similar results.
[0098] FIG. 9 shows a side-by-side comparison of photographs 1100 of feminine hygiene pads with liquid soiling applied. Each pad was placed at a 15° incline during application of the liquid soiling. Feminine hygiene pad samples 910A, 910B, and 910C had the fluid management layer of Sample 15, and feminine hygiene article samples 920A, 920B, and 920C had the fluid management layer of Sample 14. Each of Samples 910A and 920A had a film / carded nonwoven laminate topsheet and an airlaid absorbent core having a basis weight of 163 gsm. Each of Samples 910B and 920B had a film / spunbond nonwoven laminate topsheet and an airlaid absorbent core having a basis weight of 163 gsm. Each of Samples 910C and 920C had a film / carded nonwoven topsheet and an airlaid absorbent core having a basis weight of 163 gsm. The topsheets of Samples 910C and 920C had a larger open area (due to holes) than the topsheets of Samples 910A and 910B (i.e., 8 percent and 10 percent). The inventors have made additional samples constructed in accordance with the present disclosure.
[0099] Sample 16: 75 gsm spunlace: The first and second layers were homogenous and had 20 percent round viscose rayon (1.7 dtex), 30 percent polyethylene terephthalate / polyethylene bicomponent fibers (5.8 dtex), and 50 percent polyethylene terephthalate fibers (6.7 dtex), respectively. The third layer had 100 percent round viscose rayon (1.7 dtex).
[0100] Samples 14 and 16 have a higher basis weight than Sample 15. The additional basis weight helps provide a more lofty and cushion-like structure, which can provide a softness benefit to the consumer.
[0101] Absorbent articles 1A and 1B, as previously discussed, the disposable absorbent articles of the present disclosure may include a topsheet 20 and a backsheet 50. Sandwiched therebetween may be a fluid management layer 30 and an absorbent core 40. Additional layers may be disposed between the topsheet 20 and the backsheet 50.
[0102] The topsheet 20 can be joined to the backsheet 50 by attachment methods (not shown) such as those known in the art. The topsheet 20 and backsheet 50 may be directly joined to one another around the periphery of the article, or they may be indirectly joined to one another by directly joining them to the absorbent core 40, the fluid management layer 30, and / or additional layers disposed between the topsheet 20 and the backsheet 50. This indirect or direct joining can be achieved by attachment methods known in the art.
[0103] The topsheet 20 may be compliant, soft feeling, and non-irritating to the wearer's skin. Suitable topsheet materials include water-permeable materials that are oriented toward and in contact with the wearer's body to allow bodily exudates to take up and penetrate rapidly without fluids flowing back through the topsheet to the wearer's skin. The topsheet can allow for rapid movement of fluids through the topsheet while also allowing the lotion composition to migrate or transfer onto the outer or inner portions of the wearer's skin.
[0104] Suitable topsheets 20 can be made from a variety of materials, such as woven and nonwoven materials; apertured film materials, including apertured formed thermoplastic films, apertured plastic films, and interwoven fiber apertured films; hydroformed thermoplastic films; porous foams; reticulated foams; reticulated thermoplastic films; thermoplastic scrims; or combinations thereof.
[0105] Apertured film materials suitable for use as the topsheet include apertured plastic films that are non-absorbent and permeable to body exudates and that minimize or eliminate backflow of fluids through the topsheet. Other suitable formed films, including perforated and non-perforated formed films, are more fully described in U.S. Pat. No. 3,929,135, issued Dec. 30, 1975 to Thompson; U.S. Pat. No. 4,324,246, issued Apr. 13, 1982 to Mullane et al.; U.S. Pat. No. 4,342,314, issued Aug. 3, 1982 to Radel et al.; U.S. Pat. No. 4,463,045, issued Jul. 31, 1984 to Ahr et al.; U.S. Pat. No. 5,006,394, issued Apr. 9, 1991 to Baird; U.S. Pat. No. 4,609,518, issued Sep. 2, 1986 to Curro et al.; and U.S. Pat. No. 4,629,643, issued Dec. 16, 1986 to Curro et al.
[0106] Non-limiting examples of woven and non-woven materials suitable for use as a topsheet include fibrous materials made from natural fibers (e.g., cotton, including 100% organic cotton), modified natural fibers, synthetic fibers, or combinations thereof. These fibrous materials can be hydrophilic or hydrophobic, but it is preferred that the topsheet is or becomes hydrophobic. Optionally, a portion of the topsheet can be made hydrophilic using any known method of making a topsheet that contains a hydrophilic component. The nonwoven fibrous topsheet 20 may be manufactured by any known procedure for making nonwoven webs, non-limiting examples of which include spunbonding, carding, wet-laid, air-laid, melt-blown, needle-punching, mechanical entanglement, thermo-mechanical entanglement, and hydroentanglement.
[0107] The topsheet 20 can also be formed from a combination of an apertured film and a nonwoven. For example, a film web and a nonwoven web can be combined as described in U.S. Patent No. 9,700,463. Alternatively, a film can be extruded onto the nonwoven material, which is believed to enhance the contact between the film layer and the nonwoven material. Exemplary processes for such combinations are described in U.S. Patent Nos. 9,849,602 and 9,700,463.
[0108] The backsheet 50 may be positioned adjacent to the garment facing surface of the absorbent core 40 and may be joined to the garment facing surface of the absorbent core by an attachment method (not shown), such as those known in the art. For example, the backsheet 50 may be secured to the absorbent core 40 by a uniform continuous layer of adhesive, a patterned layer of adhesive, or an array of separate lines, spirals or dots of adhesive. Alternatively, the attachment method may include the use of thermal bonds, pressure bonds, ultrasonic bonds, dynamic mechanical bonds, or any other suitable attachment method or combination of these attachment methods known in the art.
[0109] The backsheet 50 may be impermeable or substantially impermeable to liquids (e.g., urine) and may be manufactured from a thin plastic film, although other flexible liquid impermeable materials may be used. As used herein, the term "flexible" refers to a material that is conformable and readily conforms to the general shape and contours of the human body. The backsheet 207 may prevent, or at least inhibit, exudates absorbed and contained in the absorbent core 205 from wetting a garment that contacts the incontinence pad 10, such as an undergarment. However, although the backsheet 50 may permit vapors to escape from the absorbent core 40 (i.e., breathable), in some cases the backsheet 50 may not permit vapors to escape (i.e., non-breathable). Thus, the backsheet 50 may comprise a polymeric film, such as a thermoplastic film of polyethylene or polypropylene. A suitable material for the backsheet 50 is, for example, a thermoplastic film having a thickness of about 0.012 mm (0.5 mil) to about 0.051 mm (2.0 mil). Any suitable backsheet known in the art may be utilized with the present invention.
[0110] The backsheet 50 acts as a barrier to any absorbed body fluids that may pass through the absorbent core 40 to the surface of the garment, thereby reducing the risk of soiling undergarments or other garments. Preferred materials are soft, smooth, flexible, liquid and vapor permeable materials that provide softness and conformability for comfort, and are low noise so that movement does not produce undesirable sounds.
[0111] Exemplary backsheets are described in U.S. Patent No. 5,885,265 (Osborn, III), issued March 23, 1999, U.S. Patent No. 6,462,251 (Cimini), issued October 8, 2002, U.S. Patent No. 6,623,464 (Bewick-Sonntag), issued September 23, 2003, or U.S. Patent No. 6,664,439 (Arndt), issued December 16, 2003. Bilayer or multilayer backsheets suitable for use herein include those exemplified in U.S. Patent Nos. 3,881,489, 4,341,216, 4,713,068, 4,818,600, European Patent Nos. 203821, 710471, 710472, and 793952.
[0112] Suitable breathable backsheets for use herein include all breathable backsheets known in the art.There are essentially two types of breathable backsheets: single-layer breathable backsheets that are breathable and waterproof, and backsheets that have at least two layers that provide both breathability and waterproofing when combined.Suitable single-layer breathable backsheets for use herein include those described in, for example, GB-A2184389, GB-A2184390, GB-A2184391, U.S. Patent No. 4,591,523, U.S. Patent No. 3,989,867, U.S. Patent No. 3,156,242, and WO 97 / 24097.
[0113] The backsheet may be a nonwoven web having a basis weight of about 20 gsm to about 50 gsm. In one embodiment, the backsheet is a relatively hydrophobic 23 gsm spunbond nonwoven web of 4 denier polypropylene fibers available from Fiberweb Neuberger under the designation F102301001. The backsheet may be coated with a water insoluble liquid swellable material as described in U.S. Patent No. 6,436,508 (Ciammaichella), issued Aug. 20, 2002.
[0114] The backsheet has a garment-facing side and an opposite body-facing side. The garment-facing side of the backsheet includes non-adhesive areas and adhesive areas. The adhesive areas may be provided by any conventional means. Pressure sensitive adhesives have generally been found to work well for this purpose.
[0115] The absorbent core 40 of the present disclosure may include any suitable shape, including, but not limited to, an oval, a discorectangle, a rectangle, an asymmetric shape, and an hourglass shape. For example, in some embodiments of the present invention, the absorbent core 205 may include a contoured shape, such as a shape in which the middle section is narrower than the end sections. As yet another example, the absorbent core may include a tapered shape having a wider portion at one end section of the pad that tapers toward a narrower end section at the other end of the pad. The absorbent core 40 may have varying stiffness in the MD and CD directions.
[0116] The configuration and structure of the absorbent core 40 may vary (e.g., the absorbent core 40 may have varying caliper areas, hydrophilic gradients, superabsorbency gradients, or acquisition zones of lower average density and lower average basis weight). Additionally, the dimensions and absorbent capacity of the absorbent core 40 may also be altered to accommodate different wearers. However, the total absorbent capacity of the absorbent core 40 should be compatible with the design load and intended use of the disposable absorbent article or incontinence pad 10.
[0117] In some forms of the invention, the absorbent core 40 can include multiple multi-functional layers in addition to the first and second laminates. For example, the absorbent core 40 can include a core wrap (not shown) useful for enclosing the first and second laminates, as well as any other layers. The core wrap can be formed by two nonwoven materials, substrates, laminates, films, or other materials. In one aspect, the core wrap can include only a single material, substrate, laminate, or other material at least partially wrapped therearound.
[0118] The absorbent core 40 of the present disclosure can include one or more adhesives, for example, to help secure the SAP or other absorbent material within the first and second laminates.
[0119] Absorbent cores containing relatively high amounts of SAP with various core designs are disclosed in U.S. Patent No. 5,599,335 to Goldman et al., European Patent No. 1,447,066 to Busam et al., International Publication No. WO 95 / 11652 to Tanzer et al., U.S. Patent Application Publication No. 2008 / 0312622(A1) to Hundorf et al., and International Publication No. WO 2012 / 052172 to Van Malderen, and can be used to construct the superabsorbent layer.
[0120] Addition of electrical potential to the core of the present disclosure is contemplated. In particular, application of electrical potential to a current multi-laminate absorbing core is described in U.S. Patent No. 4,610,678, entitled "High-Density Absorbent Structures," issued on September 9, 1986 to Weisman et al.; U.S. Patent No. 4,673,402, entitled "Absorbent Articles With Dual-Layered Cores," issued on June 16, 1987 to Weisman et al.; U.S. Patent No. 4,888,231, entitled "Absorbent Core Having A Dusting Layer," issued on December 19, 1989 to Angstadt; and U.S. Patent No. 4,834,735, entitled "High Density Absorbent Members Having Lower Density and Lower Basis Weight Acquisition Zones," issued on May 30, 1989 to Alemany et al. The absorbent core may further comprise additional layers that mimic a dual core system containing a chemically stiffened fibrous acquisition / distribution core positioned over an absorbent storage core, as detailed in U.S. Patent No. 5,234,423 and U.S. Patent No. 5,147,345, entitled "Absorbent Article With Elastic Waist Feature and Enhanced Absorbency," issued to Alemany et al. on August 10, 1993. These are useful to the extent that they do not negate or compete with these effects of the below-described laminates of the absorbent core of the present invention.
[0121] Some examples of suitable absorbent cores 40 that can be used in the absorbent articles of the present disclosure are described in U.S. Patent Application Publication Nos. 2018 / 0098893 and 2018 / 0098891.
[0122] Exemplary absorbent core configurations are shown in Figures 4-7. Figures 4 and 5 show one exemplary absorbent core configuration that may be used in combination with the fluid management layers disclosed herein. As shown, a plan view of the pad 10 is shown with the primary topsheet 20 and backsheet 50 removed to provide a better view of the absorbent core 40. Figure 5 shows an elevational view showing the absorbent system 2005 in more detail. In the configuration shown in Figures 4-7, the absorbent core 40 may include multiple layers or multiple absorbent cores. To avoid confusion, the absorbent core 40 in Figures 4-7 will be referred to as absorbent system 400.
[0123] 4 and 5, the absorbent system 400 can include a first absorbent core 460 and a second absorbent core 470. As shown, the first absorbent core 460 has a first front edge 466 and a first rear edge 467 opposite the first front edge 466. Similarly, the second absorbent core 470 has a second front edge 476 and a second rear edge 477 opposite the second front edge 476.
[0124] The first absorbent core 460 further has a first edge 361 and a second edge 363. Similarly, the second absorbent core 470 has a third edge 371 and a fourth edge 373. As shown, the first absorbent core 460 has a first width 369 and the second absorbent core 470 has a second width 379. As shown, the first width 369 can be wider than the second width 379. The respective widths of the first absorbent core 460 and the second absorbent core 470 are described below.
[0125] 5, the first absorbent core 460 has an upper surface 460A and a lower surface 460B opposite the upper surface. Similarly, the second absorbent core 470 has an upper surface 470A and a lower surface 470B. Additionally, the first absorbent core 460 and / or the second absorbent core 470 may comprise a laminated structure including multiple layers, a single layer, or a combination of layers. For example, the first absorbent core 460 may comprise a laminated structure and the second absorbent core 470 may comprise a single layer (or vice versa). Such configurations are described in more detail below.
[0126] As shown, the first absorbent core 460 can be joined to the second absorbent core 470 in an offset configuration or arrangement along the length of the absorbent system 400. As used herein, "offset" or "offset configuration" refers to the layers or laminates in question being staggered such that the leading or trailing edges of each layer or laminate do not align in the z-direction as they overlap (i.e., the leading edge of one layer or laminate does not end up with the trailing edge of the adjacent layer or laminate below or above). This offset joining configuration of the first absorbent core 460 and the second absorbent core 470 provides a joining area where the two layers overlap, forming the central portion 205C of the absorbent system 400. As a result, the two sides of the central portion 205C of the absorbent core 40 are defined by the front end portion 205F and the rear end portion 205R of the absorbent system 400. In other words, the front end portion 205F and the rear end portion 205R are disposed at opposite ends of the absorbent system 400. As shown in some embodiments, the distance between the first front end 466 and the second front edge 476 can define a length of the front end portion 205F. Similarly, the distance between the second rear edge 477 and the first rear edge 467 can define a length of the rear end portion 205R. The second front edge 476 can be a front edge of the absorbent core 40, while the first rear edge 467 can be a rear edge of the absorbent system 400.
[0127] As previously mentioned, the first absorbent core 460 and / or the second absorbent core 470 may themselves comprise multiple webs and / or layers. Referring now to Figures 4-6, for example, the first absorbent core 460 may comprise a first superabsorbent layer 461 disposed on a first distribution layer 462 (i.e., a first absorbent core laminate 760). The second absorbent core 470 may also comprise a second superabsorbent layer 471 disposed on a second distribution layer 472 (i.e., a second absorbent core laminate 770). In some embodiments, the first distribution layer 462 is joined to the second distribution layer 472 in an offset shape or configuration along the length of the core. This offset joining of the first distribution layer 462 and the second distribution layer 472 provides a joining region where the two laminates overlap, forming the central portion 405C of the absorbent system 400. As a result, the two sides of the central portion 405C of the absorbent system 400 are defined by the front end portion 405F and the rear end portion 405R of the core. In other words, the front end portion 405F and the rear end portion 405R are disposed at opposite ends of the absorbent system 400. As shown, the front end portion 405F is formed from the first front edge 466 of the first absorbent core laminate 760, and the rear end portion 405R of the core 205 is formed by the second rear edge 77 of the second absorbent core laminate 770.
[0128] The first front edge 466 of the first absorbent core laminate and the second rear edge 477 of the second absorbent core laminate are located opposite each other and form the front end portion 405F and the rear end portion 405R of the absorbent system 400, respectively (or vice versa). In another embodiment, the first rear edge 467 of the first absorbent core laminate and the second front edge 476 of the second absorbent core laminate may be located opposite each other and form the front end portion 405F and the rear end portion 405R of the absorbent system 205, respectively (or vice versa). In both cases, the first front edge 466 and the second rear edge 477 are in the form of a male connection obtained by telescopic cutting of the first and second absorbent cores. Similarly, the first rear edge 467 and the second front edge 476 are in the form of a female connection obtained by telescopic cutting of the first and second laminates.
[0129] In an alternative configuration, the first absorbent core laminate 760 may be joined to the superabsorbent layer 471 instead of the second distribution layer 472. In such a configuration, the laminates may be joined to one another in a similar offset manner, except that the first distribution layer 462 is joined to the second superabsorbent layer 471 instead of the second distribution layer 472.
[0130] In some configurations, the overlapping areas or regions forming the central portion 205C of the core 205 have at least one of the following characteristics: greater capacity, greater void volume, or greater thickness than the front and rear ends 205F, 205F, of the absorbent core 205. These configurations can be particularly useful for providing enhanced leakage protection in the central portion where female users of such pads typically contact the pad and expel fluids.
[0131] Referring again to Figures 4 and 5, as previously described, the first absorbent core 460 and / or the second absorbent core 470 may have a laminated structure. However, in some configurations, the first absorbent core 460 and the second absorbent core layer 470 may have an airlaid structure. However, the use of an airlaid structure may eliminate the need for separate distribution and superabsorbent layers. In other examples, at least one of the first absorbent core layer 460 or the second absorbent core layer 470 may include a laminated structure as described above with respect to Figure 7, and the other of the first absorbent core layer 60 or the second absorbent core layer 70 may include an airlaid structure. Suitable airlaid absorbent core structures are disclosed in U.S. Patent Nos. 8,105,301 and 8,603,622, and U.S. Patent Application Publication No. 2017 / 0348166.
[0132] 5 and 6, the first and second superabsorbent layers 461, 471 of the first and second absorbent cores 460, 470 comprise superabsorbent polymers or absorbent gelling materials (AGMs). The superabsorbent layers 461 and / or 471 may comprise a carrier web and a composition. In such a form, the superabsorbent material can be deposited on a carrier web to form the superabsorbent layer. The superabsorbent layer may comprise AGM particles or AGM fibers. Generally, the AGMs are used solely for their fluid absorbency. Such materials form hydrogels upon contact with liquids (e.g., urine, blood, etc.). Another highly preferred class of hydrogel-forming, absorbent gelling materials is based on hydrolyzed polyacids, particularly neutralized polyacrylic acids. These preferred superabsorbent polymers generally comprise substantially water-insoluble, lightly crosslinked, partially neutralized hydrogel-forming polymeric materials prepared from polymerizable, unsaturated, acid-containing monomers.
[0133] The superabsorbent layers 461 and / or 471 or portions thereof of the present disclosure may be substantially free of airfelt and therefore differ from mixed layers that may include airfelt. As used herein, "substantially free of airfelt" means less than 5%, 3%, 1%, or even 0.5% airfelt. In some forms, the superabsorbent layer may not include measurable airfelt. In the case of the first superabsorbent layer, it is preferably discontinuously disposed on the first distribution layer. The second superabsorbent layer may be discontinuously disposed on the second distribution layer in combination with or independent of the first superabsorbent layer, as previously described. As used herein, "discontinuously" or "in a discontinuous pattern" means that the superabsorbent polymer is applied to the first distribution layer in a pattern of cut shaped areas. These areas of superabsorbent polymer or areas without superabsorbent polymer may include, but are not limited to, linear strips, non-linear strips, circles, rectangles, triangles, waves, meshes, and combinations thereof. However, the first superabsorbent layer, like the second superabsorbent layer, may be disposed in a continuous pattern on the respective distribution layer. As used herein, "continuous pattern" or "continuously" refers to a material that is uninterruptedly disposed and / or secured to the superabsorbent carrier material and / or adjacent distribution layer, whereby rather the entire distribution layer is covered with superabsorbent polymer.
[0134] The first and second superabsorbent layers can include the same superabsorbent polymer. In other embodiments, the first and second superabsorbent layers can include different superabsorbent layers. This may be in addition to the different deposition patterns described above.
[0135] A superabsorbent layer having a thickness of 0.2 mm, 0.3 mm, 0.4 mm, or 0.5 mm to 1 mm, 1.2 mm, 1.4 mm, 1.8 mm, or 2 mm is provided. The first and second superabsorbent layers may have the same or different transverse widths when applied to their respective distribution layers. For example, the transverse widths of the first and second superabsorbent layers may be 20 mm, 25 mm, 30 mm, 35 mm, or 40 mm to 50 mm, 60 mm, 65 mm, 70 mm, 80 mm, or 90 mm. Alternatively, in embodiments in which the widths of the first and second superabsorbent layers differ from each other in transverse width, the first superabsorbent layer may have a smaller transverse width than the second superabsorbent layer. In particular, the first superabsorbent layer may have a transverse width that is less than about 95%, 90%, 80%, 70%, or even 60% of the second superabsorbent layer.
[0136] In certain embodiments, one or both of the first and second superabsorbent layers span greater than about 50%, 60%, 70%, 80%, 90% or even 95% of the transverse width of the superabsorbent carrier layer and / or the adjacent first or second distribution layer, respectively.
[0137] Like the optional layers that may be included in the chassis, the absorbent system may also include similar optional layers. The following description and characteristics of the optional layers are also suitable for use in the carrier web. For ease of understanding, the term "web" is intended to encompass the optional layer web and the carrier web. The optional layer web and the carrier web may be a web selected from the group consisting of fibrous structures, airlaid webs, wet-laid webs, high-loft nonwovens, needle-punched webs, hydroentangled webs, fiber tows, woven webs, knit webs, flocked webs, spunbond webs, layered spunbond / meltblown webs, carded fiber webs, coform webs of cellulose fibers and meltblown fibers, coform webs of staple fibers and meltblown fibers, and layered combinations thereof.
[0138] These optional layers and / or carrier webs may include materials such as creped cellulose batting, fluffed cellulose fibers, airfelt, and textile fibers. The web materials may also be fibers, such as, for example, synthetic fibers, thermoplastic particulates or fibers, tricomponent fibers, and bicomponent fibers, such as, for example, sheath / core fibers having the following polymer combinations: polyethylene / polypropylene, polyethylvinylacetate / polypropylene, polyethylene / polyester, polypropylene / polyester, copolyester / polyester, etc. The optional layers may be any combination of the materials listed above and / or multiple materials listed above (single or in combination).
[0139] The materials of the webs may be hydrophobic or hydrophilic depending on their placement within the chassis. The materials of these optional layers / webs may include constituent fibers including polymers such as polyethylene, polypropylene, polyester and blends thereof. The fibers may be spunbond fibers. The fibers may be meltblown fibers. The fibers may include cellulose, rayon, cotton, or other natural materials, or blends of polymers and natural materials. The fibers may also include superabsorbent materials such as polyacrylates or any combination of suitable materials. The fibers may be monocomponent, bicomponent, and / or bicomponent, non-circular (e.g., capillary channel fibers), and may have a major cross-sectional dimension (e.g., diameter of circular fibers) in the range of 0.1 to 500 micrometers. The constituent fibers of the nonwoven precursor web may also be a mixture of different fiber types, differing in characteristics such as chemistry (e.g., polyethylene and polypropylene), (mono- and bi-)component, denier (microdenier and greater than 20 denier), shape (i.e., capillary and circular), etc. The constituent fibers may range from about 0.1 denier to about 100 denier.
[0140] The web may include thermoplastic particles or fibers. The materials, particularly thermoplastic fibers, may be made from a variety of thermoplastic polymers, including polyolefins, such as polyethylene (e.g., PULPEX™) and polypropylene, polyesters, copolyesters, and copolymers of any of the foregoing.
[0141] Depending on the desired properties, suitable thermoplastic materials include hydrophobic fibers that have been rendered hydrophilic, such as surfactant-treated thermoplastic fibers or silica-treated thermoplastic fibers derived from polyolefins such as polyethylene or polypropylene, polyacrylic acid, polyamides, polystyrene, and the like. The surface of hydrophobic thermoplastic fibers can be rendered hydrophilic by treating them with a surfactant, such as a nonionic or anionic surfactant, for example, by spraying the surfactant onto the fiber, by immersing the fiber in the surfactant, or by including the surfactant as part of the polymer melt when manufacturing the thermoplastic fiber. Upon melting and resolidification, the surfactant tends to remain on the surface of the thermoplastic fiber. Suitable surfactants include nonionic surfactants such as Brij76 manufactured by ICI Americas, Inc. (Wilmington, Del.) and various surfactants sold under the Pegosperse trademark by Glyco Chemical, Inc. (Greenwich, Conn.). In addition to nonionic surfactants, anionic surfactants can also be used. These surfactants may be applied to the thermoplastic fibers at a concentration of, for example, about 0.2 to about 1 g per square centimeter of thermoplastic fiber.
[0142] Suitable thermoplastic fibers may be made from a single polymer (monocomponent fibers) or from two or more polymers (e.g., bicomponent fibers). The polymer that comprises the sheath often melts at a different, typically lower, temperature than the polymer that makes up the core. As a result, these bicomponent fibers provide thermal bonding due to the melting of the sheath polymer while retaining the desirable strength properties of the core polymer.
[0143] Bicomponent fibers suitable for use in the webs of the present disclosure may include sheath / core fibers having the following polymer combinations: polyethylene / polypropylene, polyethylvinylacetate / polypropylene, polyethylene / polyester, polypropylene / polyester, copolyester / polyester, etc. Particularly suitable bicomponent thermoplastic fibers for use herein are those having a polypropylene or polyester core and a lower melting temperature copolyester, polyethylvinylacetate, or polyethylene sheath (e.g., DANAKLON™, CELBOND™, or CHISSO™ bicomponent fibers). These bicomponent fibers may be concentric or eccentric. As used herein, the terms "concentric" and "eccentric" refer to whether the sheath has a uniform or non-uniform thickness throughout the cross-sectional area of the bicomponent fiber. Eccentric bicomponent fibers may be desirable to provide higher compressive strength at a thinner fiber thickness. Bicomponent fibers suitable for use herein may be either non-crimped (i.e., non-curved) or crimped (i.e., curved). Bicomponent fibers may be crimped by typical textile means, such as stuffer-box or gear crimp processes, to achieve a predominantly two-dimensional or "planar" crimp.
[0144] The length of the bicomponent fibers may vary depending on the particular properties desired for the fiber and web forming process. Typically, in airlaid webs, these thermoplastic fibers have lengths of about 2 mm to about 12 mm, such as about 2.5 mm to about 7.5 mm and about 3.0 mm to about 6.0 mm. Nonwoven fibers can be 5 mm to 75 mm, such as 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 55 mm, 60 mm, 65 mm, or 70 mm. The properties of these thermoplastic fibers can also be adjusted by varying the diameter (caliper) of the fiber. The diameter of these thermoplastic fibers is typically defined in terms of denier (grams per 9000 meters) or decitex (grams per 10,000 meters). When used in airlaid manufacturing machines, suitable bicomponent thermoplastic fibers can have a decitex ranging from about 1.0 to about 20 decitex, such as, for example, from about 1.4 to about 10 decitex, and from about 1.7 to about 7 decitex.
[0145] The compressive modulus of these thermoplastic materials, particularly of the thermoplastic fibers, can also be important. The compressive modulus of thermoplastic fibers is influenced not only by their length and diameter, but also by factors such as the composition and properties of the polymer or polymers from which they are made, the shape and configuration of the fiber (e.g., concentric or eccentric, crimped or uncrimped), etc. Differences in the compressive modulus of these thermoplastic fibers can be used to alter the properties, particularly the density properties, of the corresponding thermally bonded fibrous matrices.
[0146] The web may also include synthetic fibers that do not typically function as binder fibers, but which modify the mechanical properties of the fibrous web. Synthetic fibers include cellulose acetate, polyvinyl fluoride, polyvinylidene chloride, acrylics (such as Orlon), polyvinyl acetate, insoluble polyvinyl alcohol, polyethylene, polypropylene, polyamides (such as nylon), polyester, bicomponent fibers, tricomponent fibers, mixtures thereof, and the like. These may include, for example, polyester fibers, such as polyethylene terephthalate (e.g., DACRON™ and KODEL™), high melting crimped polyester fibers (e.g., KODEL™ 431 made by Eastman Chemical Co.), hydrophilic nylons (HYDROFIL™), and the like. Suitable fibers may be hydrophobic fibers that have been hydrophilized, such as surfactant-treated or silica-treated thermoplastic fibers derived from polyolefins, such as polyethylene or polypropylene, polyacrylic acid, polyamides, polystyrene, polyurethanes, and the like. In the case of unbonded thermoplastic fibers, their length may vary depending on the particular properties desired for these fibers. Typically, they have a length of about 0.3 to 7.5 cm, such as about 0.9 to about 1.5 cm. Suitable unbonded thermoplastic fibers can have a decitex in the range of about 1.5 to about 35 decitex, such as about 14 to about 20 decitex.
[0147] The first and second distribution layers are useful for wicking bodily fluids away from the wearer's skin to promote continued wear comfort after discharge. In some configurations, the support web may include a distribution layer. In some configurations, the support web may be configured similarly to the carrier web described herein. In some configurations, the first and second distribution layers of the first and second laminates are bonded not only opposite each other but also offset to form part of the core. The distribution layer includes one or more cellulose and exchanged wood pulp. It may be in the form of an airlaid. The airlaid may be chemically or thermally bonded. In particular, the airlaid may be a multi bonded airlaid (MBAL). In this example, the distribution layer may further include a fibrous thermoplastic adhesive material that at least partially bonds the airlaid to itself and to adjacent distribution layers, superabsorbent layers, or other additional (optional) layers. It should be noted that the same materials suitable for the optional layers of the chassis are envisioned to be suitable for use in the distribution layer. The basis weight of each of the first and second distribution layers ranges from 80 gsm, 80 gsm, 100 gsm, 110 gsm, 120 gsm or 130 gsm to 140 gsm, 150 gsm, 160 gsm, 180 gsm, 200 gsm, 220 gsm or 240 gsm. The preferred basis weight for each of the distribution layers of the first and second laminates is 135 gsm.
[0148] 6 and 7, as shown, the absorbent system 400 can be configured such that the first absorbent core laminate 760 includes a first superabsorbent layer 461 and a first distribution layer 462. The superabsorbent layer 461 can include a carrier layer 860 and an absorbent material 861 deposited thereon. As shown, the carrier layer 860 can have a first surface 765 and a folded surface 763. As shown, the carrier layer 860 can be folded around the first distribution layer 462 to form an L-wrap at the folded surface 763. A portion of the carrier layer 860 can be disposed between the first distribution layer 462 and the second absorbent core laminate 770.
[0149] The second absorbent laminate 770 may be similarly configured. For example, the second absorbent laminate 770 may include a second superabsorbent layer 471 and a second distribution layer 472. The second superabsorbent layer 471 may include a carrier layer 870 and an absorbent material 871 disposed thereon. As shown, the carrier layer 870 may have a second side 775 and an opposing folded side 773. The carrier layer 870 may be folded around the second distribution layer 472 to form an L-wrap at the folded side 773. A portion of the carrier layer 870 may be disposed adjacent to an underside of the second distribution layer 472.
[0150] There are several other configurations of the absorbent system 400 that can also be used. For example, the first folded surface 763 may be located on the same side of the absorbent system 400 as the second folded surface 773. In such a configuration, the second distribution layer 472 may be joined to the first distribution layer 462, or the first superabsorbent layer 461 may be joined to the second superabsorbent layer 471. In another configuration, the first superabsorbent layer 461 may be joined to the second distribution layer 472.
[0151] Fluid management layers can perform various functions with absorbent articles of the present disclosure. For example, the fluid management layers described herein can be utilized as a secondary topsheet disposed between a topsheet and an absorbent system. The fluid management layers described herein can also be utilized as a carrier layer for a superabsorbent layer described herein. Or the fluid management layers of the present disclosure can be utilized as a combination of the above functions, for example, a second topsheet and a carrier layer.
[0152] Additionally, configurations are contemplated in which the absorbent system includes only one absorbent core. The absorbent core in such configurations may include a superabsorbent layer and a distribution layer as described herein. Also, in such configurations, the carrier layer may be folded over one or both sides of the distribution layer, thereby forming a C-wrap around the distribution layer. Portions of the carrier layer may be disposed below the distribution layer.
[0153] The absorbent core 10 may further comprise barrier cuffs. Some examples of other suitable barrier cuffs are described in U.S. Patent Nos. 4,695,278, 4,704,115, 4,795,454, 4,909,803, and U.S. Patent Application Publication No. 2009 / 0312730. Additional suitable barrier cuffs are described in U.S. Patent Application Publication Nos. 2018 / 0098893 and 2018 / 0098891.
[0154] Test Method Weighing Basis weight of a test specimen is the mass in grams per unit area in square meters of a single layer of material and is measured in accordance with official method WSP130.1. A block of test specimen is cut to a known area and the mass of the specimen is measured using an analytical balance accurate to 0.0001 grams. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity, and test specimens are conditioned in this environment for at least 2 hours prior to testing.
[0155] Measurements are made on test samples taken from rolls or sheets of raw material or from layers of material excised from absorbent articles. When the layers of material are excised from the absorbent article, care is taken not to impart any contamination or deformation to the sample layers in the process. The excised layers should be free of residual adhesive. To ensure that all adhesive is removed, the layers are immersed in a suitable solvent that will dissolve the adhesive without adversely affecting the material itself. One such solvent is THF (general purpose tetrahydrofuran, CAS 109-99-9, available from any convenient source). After solvent immersion, the layers of material are allowed to air dry thoroughly in a manner that prevents unwanted stretching or other deformation of the material. After the material is dry, the test specimen is obtained. The test specimen should be as large as possible to allow for any inherent material variations to be taken into account.
[0156] Measure the dimensions of the single ply specimen using a calibrated steel metal ruler or equivalent that is traceable to NIST. Calculate the area of the specimen and record it to the nearest 0.0001 square meter. Obtain the mass of the specimen using an analytical balance and record it to the nearest 0.0001 grams. Calculate the basis weight by dividing the mass in grams by the area in square meters and record it to the nearest 0.01 grams per square meter (gsm). Repeat the test in the same manner for a total of 10 replicate specimens. Calculate the arithmetic average of the basis weight and report it to the nearest 0.01 grams per square meter.
[0157] Material composition analysis The quantitative chemical composition of test specimens containing a mixture of fiber types is determined using ISO 1833-1. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity.
[0158] The analysis is performed on test samples taken from rolls or sheets of raw material or from layers of material excised from absorbent articles. When the layers of material are excised from the absorbent article, care is taken not to contaminate or deform the sample layers in the process. The excised layers must be free of residual adhesive. To ensure that all adhesive is removed, the layers are immersed in a suitable solvent that will dissolve the adhesive without adversely affecting the material itself. One such solvent is THF (general purpose tetrahydrofuran, CAS 109-99-9, available from any convenient source). After solvent immersion, the layers of material are allowed to air dry thoroughly in a manner that prevents unwanted stretching or other deformation of the material. After the material is dried, test specimens are obtained and tested according to ISO 1833-1 to quantitatively determine its chemical composition.
[0159] Fiber decitex (Dtex) Textile webs (e.g., woven, nonwoven, airlaid) are composed of individual fibers of material. Fibers are measured in terms of linear mass density, reported in decitex. The decitex value is the mass of that fiber in grams present in 10,000 meters of fiber. The decitex value of fibers in a material web is often reported by the manufacturer as part of a specification. If the decitex value of a fiber is not known, it can be calculated by measuring the cross-sectional area of the fiber by a suitable microscopy method, such as scanning electron microscopy (SEM), determining the composition of the fiber using a suitable method, such as FT-IR (Fourier transform infrared) spectroscopy and / or DSC (Dynamic Scanning Calorimetry), and then calculating the mass of the fiber in grams present in 10,000 meters of fiber using literature values for the density of the composition. All tests are performed in a room maintained at a temperature of 23°C ± 2.0°C and a relative humidity of 50% ± 2%, and samples are conditioned under the same environmental conditions for at least 2 hours before testing.
[0160] If desired, a representative sample of the web material of interest can be cut from the absorbent article, where the web material is cut in such a way that the sample is not stretched, distorted, or contaminated.
[0161] Once the SEM images are obtained, they are analyzed as follows to determine the cross-sectional area of the fibers. To analyze the cross-section of a sample of web material, a specimen is prepared as follows: A specimen of approximately 1.5 cm (height) by 2.5 cm (length) without any folds or wrinkles is cut from the web. The sample is immersed in liquid nitrogen and an edge is broken off along the length of the specimen using a razor blade (VWR Single Edge Industrial Razor blade No. 9, surgical carbon steel). The specimen is sputter coated with gold and then attached to an SEM mount using double-sided conductive tape (Cu, 3M available from electron microscopy sciences). The specimen is oriented so that the cross-section is as perpendicular as possible to the detector to minimize oblique distortion of the cross-section being measured. SEM images are obtained with sufficient resolution to clearly show the cross-sections of the fibers present in the specimen. Fiber cross-sections vary in shape, with some fibers being composed of multiple individual filaments. Regardless, the area of each of the fiber cross sections is measured (e.g., diameter for round fibers, major and minor axes for elliptical fibers, and using image analysis for more complex shapes). If the fiber cross sections exhibit a heterogeneous cross-sectional composition, the area of each discernible component is recorded and the dtex contribution for each component is calculated and then summed. For example, if the fiber is a bicomponent fiber, the cross-sectional area is measured separately for the core and sheath, and the dtex contributions from the core and sheath, respectively, are calculated and summed. If the fiber is hollow, the inner part of the fiber, consisting of air, which does not contribute significantly to the dtex of the fiber, is excluded from the cross-sectional area. Overall, at least 100 such measurements of cross-sectional area are made for each fiber type present in the sample, and the area in square micrometers (μm 2 ) is the arithmetic mean of the cross-sectional area a k to 0.1 μm 2 Record in units.
[0162] The fiber composition is determined using a common characterization method such as FTIR spectroscopy. For more complex fiber compositions (such as polypropylene core / polyethylene sheath bicomponent fibers), a combination of common methods (e.g., FTIR spectroscopy and DSC) may be required to fully characterize the fiber composition. This process is repeated for each fiber type present in the web material.
[0163] The decitex of each fiber type in the web material. k The value is calculated as follows: d k =10000 m × α k ×ρ k ×10 -6 In the formula, d k is in grams (per 10,000 meters of calculated length), and a k The unit is μm 2 and ρ k The unit is grams per cubic centimeter (g / cm 3 The decitex is reported in 0.1 g increments (per 10,000 meters of calculated length) along with the fiber type (e.g., PP, PET, cellulose, PP / PET bicomponent).
[0164] SEM method for determining the amount of cellulose fibers A scanning electron microscope (SEM) is used to obtain images of both the first and second sides of a test sample of the material. From these images, the amount of cellulose filaments on each side of the test sample is determined using image analysis. All testing is performed in a room maintained at a temperature of 23° C.±2.0° C. and a relative humidity of 50%±2%, and samples are conditioned under the same environmental conditions for at least 2 hours prior to testing.
[0165] If necessary, test samples are obtained by removing them from the absorbent article. When the samples are excised from the absorbent article, care is taken not to impart any contamination or deformation to the sample layer during the process. Test samples are obtained from areas that do not contain folds or wrinkles. A total of six replicate test samples are obtained. The test area on each test sample is marked in a manner that will allow the same area to be analyzed on each side. One preferred method of marking the disproportion of the test area is to use an asymmetric notch.
[0166] Secondary Electron (SE) images are acquired using an SEM such as an FEI Quanta 450 (available from FEI Company, Hillsboro, OR), or equivalent. The instrument is calibrated according to the manufacturer's instructions prior to use to ensure an accurate distance scale. A test area on the first side of the test sample is observed and an image is acquired at a low magnification (e.g., 200x, approximately 1 mm horizontal field width) such that a representative number of cellulosic filaments are clearly visualized for counting purposes. An image of the second side of the test sample is taken of the same test area using the same low magnification used for the first side.
[0167] The low magnification image of the first side of the test sample is opened in image analysis software implemented on a computer, such as Image Pro Plus (available from Media Cybernetics, Rockville, MD) or equivalent. Manually count all filaments (e.g., viscose filaments) with a serrated outer surface in the image and record that number as the filament. 面1 An exemplary viscose filament 1010 is shown in FIG. 10. A sawtooth surface is shown along with distinct ends of the viscose fibers. To prevent counting a filament more than once, each counted filament is "marked" on the image. Similarly, the number of filaments with a sawtooth surface is counted on a lower magnification image of the second side of the test sample in the same test area, and that number is recorded as the number of filaments with a sawtooth surface. 面2 Record as filament 面2 The filament面1 Calculate the filament ratio by dividing by and recording in units of 1.
[0168] All measurements are repeated in the same manner for a total of six replicate samples. The arithmetic mean of the filament fraction obtained for all six replicates is calculated and reported in 1 unit.
[0169] Opacity Measurements of opacity by contrast ratio are made using a 0° / 45° spectrophotometer with an adjustable aperture that can make standard CIE color measurements using XYZ coordinates. An example of a suitable spectrophotometer is a Labscan XE (available from Hunter Associates Laboratory, Inc., Reston, VA, or equivalent). Measurements are made on a single layer of test material. All tests are performed in a room maintained at a temperature of 23° C.±2.0° C. and a relative humidity of 50%±2%, and samples are conditioned under the same environmental conditions for at least 2 hours prior to testing.
[0170] Obtain test samples by cutting from the absorbent article, if necessary. When cutting the sample from the absorbent article, care is taken not to impart any contamination or deformation to the sample layer during the process. The test sample should be obtained from an area that does not contain folds or wrinkles, but is larger than the opening used in the spectrophotometer. Note which side of the test sample faces (or is intended to face) the wearer during use. This is the side that faces the opening during testing. Obtain enough sample material to be able to make 10 measurements on non-overlapping areas of the material to be evaluated.
[0171] To measure opacity, calibrate and standardize the instrument according to the supplier's instructions using a standard black and white tile provided by the supplier, with a 1.2 inch diameter aperture. Set the spectrophotometer to use the CIE XYZ color space with D65 standard illumination, 10° observer, 1.2 inch aperture, 1.0 inch viewing area, and set the UV filter to nominal. Place the wearer-facing side of the test specimen over the aperture so that the entire opening is covered by the specimen. Place the standard white tile in direct contact with the back of the specimen and take a reading, recording the Y value as Y. 背景白 Without moving the test specimen, remove the standard white tile and replace it with the black standard tile. Take a reading and record the Y value as Y 背景黒 Record this to the nearest 0.01. 背景黒 Value Y 背景白 Calculate the opacity by dividing by the value and multiplying by 100. Record the opacity to the nearest 0.1 percent.
[0172] Repeat the same procedure on non-overlapping areas of the test sample material for a total of 10 measurements. Calculate the arithmetic mean of the opacity obtained from all 10 measurements and report to the nearest 0.1.
[0173] Tensile Test The tensile properties of the materials are measured on a constant rate of extension tensile tester (a suitable instrument is MTS Alliance using Testworks 4.0 Software, or equivalent, available from MTS Systems Corp., Eden Prairie, Minn.) using a load cell that measures forces within 1% to 99% of the cell limits. All testing is performed in a conditioned room at 23° C.±3° C. and 50%±2% relative humidity, with test specimens conditioned in this environment for at least 2 hours prior to testing.
[0174] An identical set of grips is used to hold the test specimen, one attached to the lower fixture and the other attached to the upper fixture of the tensile tester. The grips should be manual or pneumatic, lightweight, and wider than the test specimen to maximize the capacity of the load cell. The grips are constructed to allow a single line of gripping force along a line perpendicular to the tensile axis of the tensile tester. The top and bottom grips are mounted in such a way that they are aligned horizontally and vertically.
[0175] If necessary, test material is obtained by cutting from the absorbent article. When cutting the test material from the absorbent article, care is taken not to impart any contamination or deformation to the sample layer in the process. Test samples are taken from areas of the test material that do not contain folds or wrinkles. Testing is performed in the machine direction (MD) and cross direction (CD) of the test material, and each test sample is prepared as follows: The dimensions of the MD test sample are such that its length allows for a gauge length of 51.0 mm (parallel to the longitudinal axis of the absorbent article) and a width of 25.4 mm (parallel to the transverse axis of the absorbent article). The dimensions of the CD test sample are such that its length allows for a gauge length of 51.0 mm (parallel to the transverse axis of the absorbent article) and a width of 25.4 mm (parallel to the longitudinal axis of the absorbent article). When cutting the test samples, the material is not stretched or distorted. A sufficient number of test samples are prepared so that five replicates can be tested in both MD and CD.
[0176] Program the tensile tester for uniaxial extension at a constant rate of extension to break the specimen as follows: Set the nominal gage length to 51.0 mm (L) using a ruler traceable to NIST. 初期) and zero the crosshead. Insert the MD test specimen into the grips with the long side parallel to the central tensile axis of the tensile tester. Raise the crosshead at a rate of 254 mm / min until the specimen breaks, collecting force (N) and extension (mm) data at 50 Hz throughout the test. Return the crosshead to its original position. Create a graph of force (N) versus extension (mm). Read the maximum peak force (N) from the graph and record it to the nearest 0.1 N as the MD peak force. Read the extension (mm) at maximum peak force from the graph and record it as the L ピーク Record the peak MD elongation as [(L ピーク / L 初期 )*100] and record to the nearest 0.1%. Repeat the test on the CD test specimen in the same manner and report the CD peak force to the nearest 0.1 N and the peak CD elongation to the nearest 0.1%.
[0177] Repeat the test in the same manner for a total of five replicate test specimens taken in the MD and five replicate specimens taken in the CD of the test material. Calculate the arithmetic mean of the MD peak force and the CD peak force, each reported to the nearest 0.1 N. Calculate the arithmetic mean of the peak MD elongation and the peak CD elongation, each reported to the nearest 0.1%.
[0178] Caliper The caliper, or thickness, of a material is measured as the distance between a reference platform on which the material rests and a footrest that exerts a specific amount of pressure on the material for a specific period of time. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity, and test specimens are conditioned in this environment for at least 2 hours prior to testing.
[0179] The caliper is measured with a manual micrometer equipped with a footplate capable of applying a constant pressure of 0.50 kPa ± 0.01 kPa to the test sample. The manual micrometer is a deadweight instrument with an accurate reading to 0.001 mm. A suitable instrument is a Mitutoyo Series 543 ID-C Digimatic, available from VWR International, or equivalent. The footplate is a flat, grounded, circular, movable surface having a diameter smaller than the test sample and capable of applying the required pressure. A suitable footplate has a diameter of 56 mm, although smaller or larger footplates can be used depending on the size of the sample being measured. The test sample is supported by a horizontal, flat reference platform larger than and parallel to the surface of the footplate. The system is calibrated and operated according to the manufacturer's instructions.
[0180] If necessary, obtain the test sample by removing it from the absorbent article. When the test sample is excised from the absorbent article, care is taken not to impart any contamination or deformation to the test sample layer during the process. The test sample is obtained from an area that does not contain folds or wrinkles and should be larger than the presser foot.
[0181] To measure the caliper, first zero the micrometer against a horizontal flat reference platform. Place the test specimen on the platform with the test location centered under the presser foot. Gently lower the presser foot at a downward speed of 3.0 mm ± 1.0 mm / sec until full pressure is applied to the test specimen. After waiting 5 seconds, record the caliper of the test specimen to the nearest 0.01 mm. Repeat similarly for a total of five replicate test specimens. Calculate the arithmetic mean of all caliper measurements and report as thickness to the nearest 0.01 mm.
[0182] Dimensions and values disclosed herein should not be understood as being strictly limited to the exact numerical values recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."
[0183] All documents cited herein, including any cross-references or related patents or applications, are incorporated herein by reference in their entirety unless expressly excluded or otherwise limited. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest or disclose such invention, either alone or in combination with any other reference(s). Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall apply.
[0184] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.
Claims
1. 1. A fluid management layer comprising a consolidated, carded nonwoven having a basis weight of 40 grams per square meter (gsm) to 120 gsm as measured by the Basis Weight Method, the fluid management layer comprises absorbent fibers, stiffening fibers, and elastic fibers, the absorbent fibers comprising 20% to 75% by weight, the stiffening fibers comprising 1% to 50% by weight of bicomponent fibers, and the elastic fibers comprising 10% to 50% by weight, as measured by Material Composition Analysis; the absorbent fibers include cotton, rayon, or regenerated cellulose, or any combination thereof; the stiffening fibers include bicomponent fibers; The elastic fiber is a thermoplastic fiber including polypropylene or polyethylene terephthalate; the fluid management layer has a first surface and a second surface, and when an amount of cellulose fiber is measured by a SEM method, a greater amount of cellulose fiber is present on the first surface or the second surface than on the other surface; the fluid management layer includes a visual signal printed thereon; The fluid management layer exhibits a percent opacity of 48.5 to 70 percent as measured by the Opacity Method.
2. 10. The fluid management layer of claim 1, wherein the stiffening fibers comprise a dtex of from 4 to 12 as measured by the fiber decitex method.
3. The fluid management layer of any one of claims 1 to 2, wherein the fluid management layer exhibits a percent opacity of between 50 percent and 65 percent as measured by an Opacity Method.
4. The fluid management layer of any one of claims 1 to 3, wherein the ratio of absorbent fibers in the first side to absorbent fibers in the second side is from 5:1 to 1.5:
1.
5. The fluid management layer of any preceding claim, wherein the absorbent fibers on the first surface have a different decitex than the absorbent fibers on the second surface.
6. The fluid management layer of any one of claims 1 to 5, wherein the weight percentage ratio of the absorbent fibers to the stiffening fibers is from 3:1 to 1.2:
1.
7. The fluid management layer of any one of claims 1 to 6, wherein the weight percentage ratio of the absorbent fibers to the elastic fibers is from 3:1 to 1.3:
1.
8. 8. The fluid management layer of any one of the preceding claims, having an MD tensile strength of from 19N to 50N as measured by the tensile testing method.
9. The fluid management layer of any one of claims 1 to 8, having a CD tensile strength of from 5N to 15N as measured by tensile testing method.
10. A fluid management layer as described in any one of claims 1 to 9, wherein the fluid management layer comprises 20% to 75% by weight absorbent fibers.
11. The fluid management layer of any one of claims 1 to 10, wherein the fluid management layer comprises from 10% to 50% by weight of elastic fibers.
12. The fluid management layer of any one of claims 1 to 11, wherein the fluid management layer comprises from 1% to 50% by weight stiffening fibers.
13. 13. The fluid management layer of any one of the preceding claims, wherein the absorbent fibers on the first side of the fluid management layer have a greater decitex than the absorbent fibers on the second side of the fluid management layer.
14. A fluid management layer according to any preceding claim, wherein the absorbent fibres have a linear density of from 1.0 dtex to 4 dtex.
15. A fluid management layer according to any preceding claim, wherein the stiffening fibres have a linear density of from 1.7 dtex to 12 dtex.
16. The fluid management layer of any one of the preceding claims, wherein the elastic fibres have a linear density of from 4 dtex to 12 dtex.
17. The fluid management layer of any one of claims 1 to 16, wherein the fluid management layer comprises a spunlaced nonwoven.
18. 18. An adult incontinence article comprising a topsheet, a backsheet, an absorbent core disposed between the topsheet and the backsheet, and a fluid management layer according to any one of claims 1 to 17 disposed between the topsheet and the absorbent core, wherein the second side has a greater amount of cellulose fibers present than the first side, and the first side is located closer to the topsheet than the second side.
Citation Information
Patent Citations
Hydroentangled fibrous structures
US20140343523A1
Discreet disposable absorbent article
US20180098889A1